Assessment of Tertiary Teachers’ Capacity Development Need in Test Item- Writing: A Case Study of Dual Mode Institutions in the West African Sub-Region - Okonkwo, Charity A.; Akanwa, Ursala N. (West African Journal of Open and Flexible Learning, 2014)
One approach to the measurement of the quality of learning is the use of scores on standardised national or international tests or examinations when they are available as a measure of the quality of education. This study therefore examined tertiary teachers’ capacity development need in the test tern-writing necessary for enhancing assessment practices for quality education. The study employed a descriptive analytical research design. Data were collected from a sample of thirty-four participants at a train- the- trainer workshop for tertiary teachers in the West African sub- region on course material development for open and distance learners. The instrument used for data collection consisted of self- assessment exercises on test item writing requiring the participants to self- describe/assess their level of assessment literacy pertaining to two general categories of test items - construction of essay test items requiring higher order thinking skills and objective test items. The self -assessment exercises were developed as source book content derived from standards developed by the National Centre for Research and Evaluation, Standards and Student Testing (Clay, 2001) and were adopted and used for data collection in this study. Five objectives and three research questions guided the study. The data collected in respect of the research questions were analysed using descriptive statistics - frequencies and percentages. The findings indicated the areas of need for the tertiary teachers’ capacity development in test item-writing. The needed professional development is necessary to enable the results from their test items used for measurement purposes to reflect the quality of learning. Recommendations were made for improvement and for continuing capacity building and enhancement of tertiary teachers on test item-writing.